Method of Biophysical Express-estimation of the Abundance, Biomass and Spatial Distribution of the Antarctic Kril Population - Yu. N. Tokarev; V. I. Vasilenko; B. G. Sokolov; V. F. Zhuk; D. Ya. Slipetsky (Ukrainian Antarctic Journal, 2004)
The new method of express-estimation of the Antarctic krill (Euphausia superba Dana) spatial distribution and biomass has been worked out and tested during the 7-th Antarctic Ukrainian scientific expedition. The method is based on the amplitudinal characteristics of the biophysical (bioluminescence and acoustic) fields. The hydroacoustical search and registration of krill population in the upper 200-m layer was used on drift and vessel moving using the apparatus complexes “SKAT” and “PLANKTON-3”. Simultaneously the method of multiple bioluminescence sounding of the euphotic layer (0-100 m) by hydrobiophysical complex “SALPA” was used. This permit to was used to specify systematic affiliation of the hydroacoustically revealed objects accumulations and evaluate more correctly the luminous plankton spatial distribution. Some examples of the method application in the Antarctic sector of Atlantic are given.